2011
DOI: 10.5505/1304.7361.2011.49344
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between The Intensity Of Chest Pain Of The People Who Applied To Emergency Room With Their Chest Pain Complaints With St Segment Changes And Acute Coronary Syndrome

Abstract: SUMMARY Objectives In this study, we aimed to reveal the relationship between the intensity of chest pain and likelihood of ACS and ST segment deviation in electrocardiography (ECG) of the patients who presented with chest-pain. Methods Total ÖZET AmaçÇalışmamızda, acil servise göğüs ağrısı ile başvuran hastaların, gö-ğüs ağrısı şiddeti ile eşzamanlı EKG'de bulunan ST segmenti deği-şikliklerinin ilişkisini ve akut koroner sendrom (AKS) olasılığını ortaya koymak amaçlandı. Gereç ve YöntemÇalışmaya acil servise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The older age and male gender are consistent risk factors of ACS. In several studies, both of them found to be related with ACS (10,(19)(20)(21). Similarly, the significant association between ACS and older age was presented in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The older age and male gender are consistent risk factors of ACS. In several studies, both of them found to be related with ACS (10,(19)(20)(21). Similarly, the significant association between ACS and older age was presented in this study.…”
Section: Discussionsupporting
confidence: 86%